2010
DOI: 10.4018/jwltt.2010070102
|View full text |Cite
|
Sign up to set email alerts
|

The Blended Learning Ecosystem of an Academic Institution in Greece

Abstract: Blended learning has been recognized as the most promising emerging trend in higher education, offering new capabilities, as it may significantly enhance the interaction and communication between instructors and students. The challenge of blended learning is to balance weaknesses and strengths of face-to-face and e-learning teaching environments and effectively combining them to provide enhanced learning capabilities. Its success should benefit instructor-student relation. To this end, the authors adopt ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Contrary to these negative perceptions, most of the students thought that the video lectures did not really prevent them from attending classes at University but helped them complementary to the face to face lecture. This conclusion conforms to the conclusions drawn by the studies of Chalkias and Anagnostopoulos ( 2004 ) and Nikolaidou et al ( 2010 ) in Harokopio University but not agree with Verdanakis et al (2009). The evaluation revealed that students wanted the video lectures to be expanded in workshops and not only in theoretical lessons.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Contrary to these negative perceptions, most of the students thought that the video lectures did not really prevent them from attending classes at University but helped them complementary to the face to face lecture. This conclusion conforms to the conclusions drawn by the studies of Chalkias and Anagnostopoulos ( 2004 ) and Nikolaidou et al ( 2010 ) in Harokopio University but not agree with Verdanakis et al (2009). The evaluation revealed that students wanted the video lectures to be expanded in workshops and not only in theoretical lessons.…”
Section: Discussionsupporting
confidence: 78%
“…Chalkias and Anagnostopoulos ( 2004 ) and Nikolaidou et al ( 2010 ) describe the usage of Open eClass in Harokopio University. The latter authors have conducted an evaluation study of the LMS with the participation of students, instructors and infrastructure-technology specialists to evaluate the ecosystem of blended learning.…”
Section: Evaluating the Use Of Lms In Higher Education In Greecementioning
confidence: 99%
See 1 more Smart Citation
“…Literature has covered the benefits of b-learning broadly. b-learning combines both technology and traditional educational approaches, thus enables having rich content in the courses, flexible way to access the content, and creating alternative communication channels [14]- [16]. B-learning also supports traditional educational in terms of management, evaluation, monitoring, and administering courses by using technology [17].…”
Section: Introductionmentioning
confidence: 99%
“…By this, it is mean that online learning activities became another alternative of learning, instead only in the class. The learning process through technological advantages may involve traditional study in the classroom and e-learning combination environment which is also called as blended learning [2], [3].…”
Section: Introductionmentioning
confidence: 99%